Si amanece, nos vamos for solo guitar: Using multiphonics in a new way - Torres, Rita (Revista Vórtex, 2020)
The technique of guitar multiphonics is an unconventional performing technique that gives rise to sounds of unusual colours, in which it is easier to perceive multiple pitches. In most compositions that employ the technique, this is done conventionally – there is hardly any variation in the beginning and/or end of the sounds. The piece presented in this article uses multiphonics in a new way. This was arrived at by the author unintentionally when conducting artistic research during the compositional process of the third piece in which she used guitar multiphonics. With the new form of usage of this technique there is variation in both the beginning and end of the sounds, as these gradually arise from, and vanish into the continuous sound of an open string. In the piece, this is used as a pedal tone that sounds insistently most of the time.